Content analysis of European library and information science journals - Shevtsova, Yuliia; Shemaieva, Hanna (Technium Social Sciences Journal, 2020)
Content analysis of 28 library and information science journals of the leading European countries has been conducted in the context of the current research. The thematic focus of these journals has been the priority of the research. Several thematic groups of library and information science journals have been identified. They include the journals that cover the following topics related to: 1) digital information; 2) development of information and communication technologies and their application in library practice; 3) library and information with the key topic of library and information management; 4) various types of communication. The conclusion has been made that scholarly interdisciplinary communication is expanding in the context of information society development. The analysis provides means for taking into account the trends in the leading European countries that help to evaluate and compare the performance of Ukrainian libraries and increase the level of professional knowledge and communication of library and information science professionals.